Lidocaine Enhances Contractile Function of Ischemic Myocardial Regions in Mouse Model of Sustained Myocardial Ischemia. - Björn Müller-Edenborn; Gabriela Kania; Elena Osto; Philipp Jakob; Nazmi Krasniqi; Beatrice Beck-Schimmer; Przemyslaw Blyszczuk; Urs Eriksson (PLoS ONE, 2016)
RATIONALE:Perioperative myocardial ischemia is common in high-risk patients. The use of interventional revascularisation or even thrombolysis is limited in this patient subset due to exceedingly high bleeding risks. Blockade of voltage-gated sodium channels (VGSC) with lidocaine had been suggested to reduce infarct size and cardiomyocyte cell death in ischemia/reperfusion models. However, the impact of lidocaine on cardiac function during sustained ischemia still remains unclear. METHODS:Sustained myocardial ischemia was induced by ligation of the left anterior descending artery in 12-16 weeks old male BALB/c mice. Subcutaneous lidocaine (30 mg/kg) was used to block VGSC. Cardiac function was quantified at baseline and at 72h by conventional and speckle-tracking based echocardiography to allow high-sensitivity in vivo phenotyping. Infarct size and cardiomyocyte cell death were assessed post mortem histologically and indirectly using troponin measurements. RESULTS:Ischemia strongly impaired both, global systolic and diastolic function, which were partially rescued in lidocaine treated in mice. No differences regarding infarct size and cardiomyocyte cell death were observed. Mechanistically, and as shown with speckle-tracking analysis, lidocaine specifically improves residual contractility in the ischemic but not in the remote, non-ischemic myocardium. CONCLUSION:VGSC blockade with lidocaine rescues function of ischemic myocardium as a potential bridging to revascularisation in the setting of perioperative myocardial ischemia.